TRADE MARGINS OF PRESCRIPTION MEDICINES IN LIBERALISED AND NON-LIBERALISED PHARMACY MARKETS (EU 28 + NORWAY) - Písek, Jaroslav; Pícha, Kamil (MELANDRIUM, 2018)
Objectives: To analyse the pharmacy margin in the EU 28 and Norway. To determinate a correlation between margin, GDP and the percentage of chain pharmacies (degree of liberalisation of pharmacy market). Methods: Systematic review of the margin regulations applicable to community pharmacies. Calculation the margin for the medicine at the ex-manufacturer price of CZK 150 (€ 5.92). Visualization and comparison of information obtained in MS Excel. Regression analysis (general linear model) of processed data. Results: The Czech pharmaceutical distribution market is fully liberalised and horizontally and vertically integrated. 35% of the Czech community pharmacies are associated in chains. Pharmacy chains are active in 18 EU countries. In six EU countries, chains operate more than 50% of community pharmacies (Sweden, the Baltic States, the UK and Croatia). Norway currently has 86.6% of pharmacies associated with vertically integrated companies controlled by the three largest pharmacy chains (and wholesalers) in Europe. In nine other EU countries, at least one of these companies (Walgreens, Phoenix and McKesson) operates one of the three largest pharmacy chains. Walgreens, Phoenix and McKesson own over 7,000 pharmacies in the countries surveyed. Pharmacy chains are not legally permitted in eight EU countries, where 42% of all EU pharmacies operate. The average margin is 27.2% in the monitored countries. The minimum margin is 7% (Croatia), and the maximum is 59.8% (Germany). The mean of margins for countries with chains is 25.6% and for countries without chains is 29.7%. The statistical model indicates the positive correlation between margins and GDP. We did not find a clear association between the margin and the degree of liberalisation. Conclusion: A reduction in margins does not follow the deregulation of pharmacy market. The hypothesis that liberalisation brings lower costs to the healthcare payers was not confirmed.
Obchodní marže preskripčních léčiv na liberalizovaných a neliberalizovaných lékárenských trzích
Keywords: pharmacies; margin; EU 28; liberalisation; lékárny; marže; EU 28; liberalizace